Manpower Planning for Local Labor Markets - Sexton, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Manpower Planning for Local Labor Markets" by Garth L. Mangum and David Snedeker.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z